Tale of a plaster – Different versions of a story and possible meaning of the phrase Lo shmiʿa li (Bavli Eruvin 102b) - Zur, Uri (HTS teologiese studies, 2020)
This article deals with different versions of a story in Tractate Eruvin of the Babylonian Talmud (102b). This story has different versions in various sources, including in one page from the Genizah fragment Cambridge U-L T-S F2 (2) 23, numbered C98948 in the Friedberg Jewish Manuscript Society. Each version changes our understanding of the story’s content, and in this article we will display these variations and examine the feasibility that they reflect about the original version. The story ends with the phrase Lo shamiʿa li, for which we shall offer a new alternative meaning.Contribution: The main contribution of this article is in revealing the importance of comparing the different versions to the same story which implies a change in the content of the story. This has future implications when considering a story that has different versions. In addition, exploring and examining a particular phrase can offer a different interpretation or meaning than it was commonly thought. These insights are based on story and phrase found in the theological text, so that the article fits to the focus and scope of this journal.